1994
DOI: 10.1161/01.cir.90.6.2679
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin formation and degradation in patients with arteriosclerotic disease.

Abstract: There is evidence of enhanced thrombin formation in patients with PAD compared with an age- and sex-matched control group without clinical and sonographic evidence of arteriosclerosis. The thrombin formed, however, appears to be almost completely neutralized by antithrombin III. No direct evidence of fibrin formation was obtained, since the FPA concentrations were not different. In the patients with PAD, the higher concentrations of D-dimers are indicative of in vivo fibrinolysis. Thus, some fibrin formation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 9 publications
0
41
3
Order By: Relevance
“…17,18 The effect of exercise on hemostasis in patients with peripheral arterial disease has also been studied previously. 19 In contrast to our results, the PAOD patients in the study by Herren et al 19 showed enhanced thrombin formation (TAT) at rest compared with the age-and sex-matched healthy control group. Differences between the study populations may explain this dissimilarity: PAOD in the patients in the study by Herren et al 19 was more severe than in our patient group; at the same time, the share of current smokers and hypertensives among their patients was significantly higher than in their control group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…17,18 The effect of exercise on hemostasis in patients with peripheral arterial disease has also been studied previously. 19 In contrast to our results, the PAOD patients in the study by Herren et al 19 showed enhanced thrombin formation (TAT) at rest compared with the age-and sex-matched healthy control group. Differences between the study populations may explain this dissimilarity: PAOD in the patients in the study by Herren et al 19 was more severe than in our patient group; at the same time, the share of current smokers and hypertensives among their patients was significantly higher than in their control group.…”
Section: Discussioncontrasting
confidence: 99%
“…19 In contrast to our results, the PAOD patients in the study by Herren et al 19 showed enhanced thrombin formation (TAT) at rest compared with the age-and sex-matched healthy control group. Differences between the study populations may explain this dissimilarity: PAOD in the patients in the study by Herren et al 19 was more severe than in our patient group; at the same time, the share of current smokers and hypertensives among their patients was significantly higher than in their control group. Additionally, Herren et al 19 did not see any elevation of D-dimer or TAT after exercise, a result that also differed from ours.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding of higher plasma fibrin D-dimer levels in the sedentary postmenopausal compared with premenopausal women is consistent with previous studies 7,22 and supports the premise of increased fibrin formation and deposition with age. 45,46 An original finding of the present study, however, was that regular physical activity does not appear to influence the effect of age on plasma fibrin D-dimer levels. Although the physically active postmenopausal women demonstrated lower absolute plasma fibrin D-dimer levels than their sedentary age-matched peers, they had significantly higher fibrin D-dimer levels than their younger counterparts.…”
Section: Fibrin D-dimermentioning
confidence: 49%